Rancang Model Rantai Pasok Tepung Pisang Sebagai Upaya Meningkatkan Nilai Tambah Komoditas Pisang di Kota Madiun - Chatarina Dian Indrawati (Widya Teknik, 2021)
The demand for bananas as fresh fruit and as raw material for food processing products in Madiun City is not only fulfilled by banana production from the city of Madiun. The regency area around the city of Madiun has a major contribution in meeting the need for bananas in the city of Madiun. Among them are the Madiun district, namely Dungus, Kare, Dolopo districts and the Ngawi district, namely Ngawi district, Magetan district, namely Takeran sub-district, Ponorogo district, namely Ponorogo district, Bojonegoro district, and Blora districtProcessing bananas into banana flour is an effort to increase the absorption capacity of banana production and provide added value to banana commodities. Freshly harvested bananas are bananas that are still unripe with the characteristics of the fruit is still hard and has a high starch content. When the bananas are in new harvest conditions, they can be processed into banana flour.The demand for flour in the local area of Madiun City has not been proven to be significant as seen from the retail traders who have not provided banana flour. Food processing businesses in Madiun City are not familiar with the use of banana flour as a food raw material. Banana flour marketing can be done through online marketplaces such as Tokopedia, Shopee, and Blibli.The results of the study concluded that the critical factor of the supply chain for bananas and banana flour is on the farmer's side, where the cropping pattern of the farmers can be coordinated in relation to the timing and type of banana. Coordination requires synergy with government agencies and farmer group institutions. Market share at the banana farmer level is quite efficient, at 42-67%. The margin for the banana flour product is Rp. 5,625 / kg with an added value of 0.48%.